Electrodeposition of selective coatings based on black nickel for flat-plate solar water heaters. (December 2019) - Lizama-Tzec, F.I.; Herrera-Zamora, D.M.; Arés-Muzio, O.; Gómez-Espinoza, V.H.; Santos-González, I.; Cetina-Dorantes, M.; Vega-Poot, A.G.; García-Valladares, O.; Oskam, G.
Graphical abstract: Highlights: Electrodeposition of black nickel selective coatings has been scaled up. Passivation of the backside of the copper substrates improves the stability. Solar absorptance and thermal emittance affect collector performance. An electrodeposited 1.74 m 2 solar collector has been fabricated. Electrodeposited collector performance compares well with commercial collectors. Abstract: The selective coating is the heart of a solar heating system, where the coating needs to efficiently absorb sunlight and heat up the substrate, which subsequently transfers the generated heat to a fluid. Selective coatings generally have an IR reflecting interlayer that maintains low thermal emittance from the substrate in order to optimize the thermal efficiency of the collector. We report on the electrodeposition of a bright nickel/black nickel selective coating onto a copper solar collector substrate, and compare the optical properties and thermal stability with commercially available options, including copper oxide and sputter-deposited nitrogen-doped titanium dioxide. We have fabricated identical solar collectors of an aperture area of 1.74 m 2 in order to compare the performance of the three selective coatings, and we have determined the thermal efficiency versus temperature difference in a realistic outdoor setting under sunlight. The collector with the electrodeposited selective coating shows overall better performance than the copper oxide-based collector, and at temperatures above about 50 °C, it achieves equal performance as the titanium dioxide-based collector. One of the reasons for the lower thermal losses for the electrodeposited collector appears to be the protection of the backside of the copper flat plates with a nickel coating. Taking the low investment and materials cost into account, the electrodeposited black nickel/bright nickel/copper flat-plate collector may be attractive for commercial implementation in solar water heaters.